Phototherapy‐induced blistering reaction and eruptive melanocytic nevi in a child with transient neonatal porphyrinemia. Issue 5 (1st July 2018) - Karg, Eszter; Kovács, László; Ignácz, Ferenc; Varga, Erika; Hocsi, Mária; Szűts, Péter; Kemény, Lajos; Bereczki, Csaba; Oláh, Judit
Abstract: Neonatal blue‐light phototherapy induced a blistering reaction followed by eruption of melanocytic nevi on the exposed skin surface of a child with transient neonatal porphyrinemia. New nevi are still developing 4 years after the triggering event. The role of phototoxicity‐induced epidermal injury, that of porphyrins and the influence of neonatal blue‐light therapy, in this unique phenomenon are discussed.